Introduction to electrodynamics - Griffiths, David J. (New Delhi: Cambridge University Press, 2017)
his book is an elegant introductory text to serve the needs of undergraduate courses in physics. A highly successful textbook is now fine-tuned to provide further clarity and precision in its third edition. It provides a clear, precise and accessible coverage of fundamentals of electromagnetic theory through lucid exposition, logical organization, and sound pedagogical order. Standard topics are dealt with exclusively in the domain of classical mechanics, save for the last chapter, although electrodynamics extends with unique simplicity to the other three realms of mechanics. A large collection of fully- worked examples and numerous problems promote comprehension and retention of the material studied.
Appendix A-C, 547-561p.; Index 562-576p.
Keywords: Electrodynamics; Physics